COMMUNICATIVE COMPETENCE OF THE TEACHER AS A DETERMINING COMPONENT OF MODERN EDUCATION - Romashchenko І. В. (Pedagogy of Higher and Secondary Education, 2022)
Article is devoted to actual processes of formation of professional competence of teachers in a competitive educational environment, the need to explore and use language to ensure effective implementation of communicative intentions.